2017
DOI: 10.1158/2326-6066.cir-16-0264
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Neoantigens Can Induce CD8+ T-Cell Responses and Antitumor Immunity

Abstract: Next-generation sequencing technologies have provided insights into the biology and mutational landscape of cancer. Here we evaluate the relevance of cancer neoantigens in human breast cancers. Using patient-derived xenografts from three patients with advanced breast cancer (xenografts were designated as WHIM30, WHIM35, and WHIM37), we sequenced exomes of tumor and patient-matched normal cells. We identified 2091 (WHIM30), 354 (WHIM35), and 235 (WHIM37) nonsynonymous somatic mutations. A computational analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…In fact, both the burden of tumor mutations and the load of neo-epitopes represent two of the factors that are linked to response to checkpoint inhibitors in different malignancies like melanoma or lung cancer [63]. However, although tumor neoantigens that are produced as a result of breast cancer cells' genomic instability can be recognized by the immune system and induce T-cell responses and antitumor immunity [62,64], the immunogenicity of breast cancer can be rather heterogeneous, depending to a large extent on the specific subtype of breast cancer [65].…”
Section: Breast Tumor Microenvironmentmentioning
confidence: 99%
“…In fact, both the burden of tumor mutations and the load of neo-epitopes represent two of the factors that are linked to response to checkpoint inhibitors in different malignancies like melanoma or lung cancer [63]. However, although tumor neoantigens that are produced as a result of breast cancer cells' genomic instability can be recognized by the immune system and induce T-cell responses and antitumor immunity [62,64], the immunogenicity of breast cancer can be rather heterogeneous, depending to a large extent on the specific subtype of breast cancer [65].…”
Section: Breast Tumor Microenvironmentmentioning
confidence: 99%
“…Furthermore, immunocompetent cells are able to recognize TSAs/ neoepitopes as being foreign [27]. It was shown that TILs, especially cytotoxic T cells, recognize TSAs/neoepitopes in breast cancer and are able to induce antitumor responses in mice [28]. However, the knowledge about somatic mutations causing tumor regression is limited [29] and might be unique for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…In a small group of patients with stages III and IV melanoma, Ott et al demonstrated only 16% neoantigens, which were predicted by NetMHCpan-2.4 algorithm, were recognized by CD8 + T cell [37]. Zhang et al found a significant T-cell response in two of nine neoantigens for one breast cancer patient, and one of eight neoantigens for the other two patients with breast cancer, in which neoantigens were predicted by NetMHC-3.2 algorithm [38]. Therefore, we considered that none of the current algorithms was perfect, and it was necessary to simultaneously use multiple algorithms to increase the accuracy of peptide binding affinity prediction.…”
Section: Discussionmentioning
confidence: 99%